2020
DOI: 10.1080/09286586.2020.1823425
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment, Eye Disease, and the 3-year Incidence of Depressive Symptoms: The Canadian Longitudinal Study on Aging

Abstract: Purpose: Our goal was to explore the longitudinal association between vision-related variables and incident depressive symptoms in a community-dwelling sample of older adults and to examine whether sex, education, or hearing loss act as effect modifiers. Methods: A 3-year prospective cohort study was performed using data from the Canadian Longitudinal Study on Aging consisting of 30,097 individuals aged 45-85 years. Visual acuity was evaluated with habitual distance correction using an illuminated Early Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…5 The full methods and results on the association of visual impairment, eye disease, and the incidence of depressive symptoms are published in another paper. 6…”
Section: Introductionmentioning
confidence: 99%
“…5 The full methods and results on the association of visual impairment, eye disease, and the incidence of depressive symptoms are published in another paper. 6…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed anxiety or depression in cataract patients 2 , 4 , 12 23 (Table 1 ). These studies consistently indicate that cataract patients experience more severe anxiety and depression compared to healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Our results revealed that participants with only vision impairments, only hearing impairments, and both vision and hearing impairments presented with depressive symptoms but with a different degree of risk. Several population-based longitudinal studies in Canada ( 25 ), the Salisbury Eye Evaluation Study ( 26 ), and the National Health and Aging Trends Study ( 27 ) confirmed a link between depressive symptoms and vision impairments. A prevailing concern among hearing-impaired individuals in China is the impact of hearing impairments on physical and mental health ( 23 , 28 ).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the Korean health insurance cohort study ( 29 ) reported that severe hearing impairments significantly increased the risk of depressive symptoms in all age groups of the study population after matching for age, sex, income, and region. A population-based longitudinal study reported that vision and hearing impairments were significantly associated with depressive symptoms and suggested that treating or rehabilitating either vision or hearing impairments may incident depressive symptoms ( 25 , 30 , 31 ). According to several prospective studies, the presence of depressive symptoms is associated with reduced sensory function, and the risk of depressive symptoms increases over subsequent years ( 28 , 32 ).…”
Section: Discussionmentioning
confidence: 99%